Perancangan Minus One Instrumen Keroncong pada Lagu Keroncong Moresko Karya Kusbini - Mei Artanto (Institut Seni Indonesia Denpasar, 2021)
Purpose: There is only limited literature dealing with the minus-one design process, especially for the seven keroncong instruments. The writer wants to know the minus one design process for Kusbini's Kerocong Moresco song, both conceptually and technically. Research methods: This qualitative research employs an observation, interview, and documentation as the research instrumens to gather the data, and support the research results and findings which the data will then be verified using perspectives in musicology that focus on intra-aesthetic aspects, for instance, musical forms, individual performance techniques, and ensembles. Results and discussion: The process of designing a minus one for keroncong instrumen uses multitrack recording to maintain the intra-esthetic aspects of keroncong music in Kusbini's Keroncong Moresko song. Implication: The current Covid-19 pandemic is not a barrier to continuing to do keroncong music activities, especially in terms of learning music